Literature Review : Efektivitas Terapi Tertawa Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi Tahun 2021 - Maya Kumala Sari; Nur Elly; Dahrizal Dahrizal (Gayaku Publisher, 2022)
Hypertension, which is commonly referred to by the general public as high blood pressure, is a chronic disease that is often called a stlent killer, namely (a silent killer) because in general patients do not know tat they have hypertension before checking their blood pressure. The purpose of this study was to determine the effect of laughter therapy. On reducing blood pressure in hypertensive patients based on literature review. The database sources used are from Google Scholar, Pubmed, Google Advance Search. The population in this study were 13 journals from 2013-2019 with research methods using Pre Exsperimental, Quasy Experiment, the resultd obtained that the average has a systolic blood pressure of 135,71 mmHg and a diastolic blood pressure of 71,45 mmHg and statistical test results with the results of systolic blood pressure p=0,000 to 0.02 where <0,05 and diastolic blood pressure p=0,000 to 0,03 where <0,05, which means that is a significant difference in vane right blood before and after laughter therapy.